2022
DOI: 10.1186/s12871-022-01677-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of low-dose morphine intrathecal analgesia and sufentanil PCIA in elderly patients with hip fracture undergoing single spinal anesthesia — a randomized clinical trial

Abstract: Background The complications of postoperative pain, such as hypertension, hypermetabolism, irritability, and postoperative cognitive dysfunction, significantly affect the postoperative rehabilitation of elderly patients. Intrathecal morphine prolongs analgesia after surgery, but has been implicated in nausea and vomiting, pruritus, postoperative respiratory depression, or apneic episodes. The present study explored the effect and safety of low-dose morphine used adjunctively with bupivacaine du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Sufentanil, a thiophene derivative of fentanyl, is known for its ability to easily cross the blood-brain barrier and has a long duration of action. It rapidly reaches peak drug concentration [12,13] , and is commonly used as a postoperative analgesic in clinical practice. However, highdose administration can result in various adverse reactions, including excessive sedation, dizziness, gastrointestinal dysfunction, severe respiratory suppression, and even death [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Sufentanil, a thiophene derivative of fentanyl, is known for its ability to easily cross the blood-brain barrier and has a long duration of action. It rapidly reaches peak drug concentration [12,13] , and is commonly used as a postoperative analgesic in clinical practice. However, highdose administration can result in various adverse reactions, including excessive sedation, dizziness, gastrointestinal dysfunction, severe respiratory suppression, and even death [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Although opioid administration can itself be a risk factor for POD (Duprey et al, 2021), pain is probably a stronger POD trigger in geriatric patients with hip fractures (Morrison et al, 2003). Two RCTs compared morphine and oxycodone to sufentanil respectively, and they found that both low-dose morphine intrathecal analgesia and oxycodone patient-controlled intravenous analgesia are superior to sufentanil patient-controlled intravenous analgesia in the prevention of POD in geriatric patients with hip fractures (Gan et al, 2020;Xu et al, 2022). Therefore, multimodal analgesia is recommended for the management of POD in geriatric patients with hip fractures.…”
Section: Analgesicsmentioning
confidence: 99%
“…[12] The downsides of intravenous administration include high dosage, limited analgesic efficacy, and the possibility of severe postoperative nausea and vomiting. [13] This paper prospectively analyzes the effects of different analgesic methods on pulmonary function after the hip fracture in the elderly.…”
Section: Introductionmentioning
confidence: 99%